P437 Higher adalimumab maintenance regimens are more effective than standard maintenance doses in Crohn's disease patients who have failed infliximab. (16th January 2018) - Narula, N; Greener, T; Boland, K; Steinhart, A H; Silverberg, M
Abstract: Background: Many Crohn's disease (CD) patients who are treated with anti-TNF therapies experience a loss of response (LOR) over time and require dose escalation. The efficacy and safety of treating CD patients with higher maintenance regimens of adalimumab following induction remains unknown. Methods: We conducted a retrospective observational study with CD patients receiving adalimumab for luminal and perianal disease between 2007 and 2017 at a tertiary care IBD centre. Patients were categorised according to their maintenance regimen; 40 mg weekly, 80 mg every other week (EOW), or greater was defined as a high dose maintenance regimen (HD) and 40 mg EOW was defined as standard regimen (SD). All patients in HD group were started on high-maintenance doses directly after induction. The primary outcome was time to treatment failure, defined as non-response, loss of response (LOR) with no benefit from dose optimisation, adverse event requiring discontinuation or surgery. Cox proportional hazards regression was performed to adjust for potential confounders. Results: We identified 39 patients that were started on HD regimens following induction and compared them to 40 patients that received SD maintenance. All subjects had previously been exposed to infliximab. According to a Kaplan–Meier survival curve analysis, time to treatment failure was significantly longer in patients in the HD group ( p = 0.0015). Patients on HD adalimumab had a lower hazard rate of treatment failure (HR 0.21, p = 0.0005) when compared with patients on SD, after adjusting for induction dose and concomitant immunomodulator use. There was also a trend towards reduced failure in patients using concomitant immunomodulators, when adjusted for all other covariates (HR 0.48, p = 0.06). Patients in the HD group were more likely to achieve clinical remission at 3 and 12 months (89% vs. 25%, p < 0.001 and 69% vs. 31%, p = 0.003, respectively). Patients in the SD group were more likely to require IBD-related surgery or therapy optimisation (18% vs. 3%, p = 0.03 and 55% vs. 33%, p = 0.05). No difference in adverse events was identified between the groups (31% vs. 30%, p = 0.94). Conclusions: Higher dose maintenance regimens were more effective than the standard adalimumab maintenance protocol with better short-term and long-term clinical outcomes.